How to build better memory training games - Deveau, Jenni; Jaeggi, Susanne M.; Zordan, Victor; Phung, Calvin; Seitz, Aaron R. (Frontiers in Systems Neuroscience, 2015)
Can we create engaging training programs that improve working memory (WM) skills? While there are numerous procedures that attempt to do so, there is a great deal of controversy regarding their efficacy. Nonetheless, recent meta-analytic evidence shows consistent improvements across studies on lab-based tasks generalizing beyond the specific training effects (Au et al., 2014; Karbach & Verhaeghen, 2014), however, there is little research into how WM training aids participants in their daily life. Here we propose that incorporating design principles from the fields of Perceptual Learning and Computer Science might augment the efficacy of WM training, and ultimately lead to greater learning and transfer. In particular, the field of perceptual learning has identified numerous mechanisms (including attention, reinforcement, multisensory facilitation and multi-stimulus training) that promote brain plasticity. Also, computer science has made great progress in the scientific approach to game design that can be used to create engaging environments for learning. We suggest that approaches integrating knowledge across these fields may lead to a more effective WM interventions and better reflect real world conditions.